Phytochemical Screening, Proximate Composition, and Mineral Analysis of Tropical Almond (Terminalia catappa) Seeds Collected from Gombe State, Nigeria - Maryam Usman Abdulkadir; Farida Muhammad Mijinyawa; Abubakar Muhammad Hammari; Adamu Jauro Abubakar; Ibrahim Abubakar Adam; Saminu Yusuf; Hanifah Yakubu (Asian Journal of Science, Technology, Engineering, and Art, 2026)
The growing demand for natural medicines and plant-derived nutrients has increased scholarly interest in botanical resources rich in bioactive constituents, minerals, phytochemicals, and other metabolites. Terminalia catappa, a member of the Combretaceae family commonly found in tropical and subtropical regions, is traditionally used for its antioxidant, anti-inflammatory, anticancer, and antidiarrheal properties. This study aimed to evaluate the phytochemical profile, proximate composition, and mineral content of T. catappa seed nuts. Standard analytical methods were employed for proximate analysis, while elemental content was determined using atomic absorption spectrophotometry and flame photometry. Phytochemical screening revealed the presence of saponins, steroids, phenols, and alkaloids, whereas tannins and flavonoids were absent. The proximate composition showed moisture content of 11.03%, ash content of 5.00%, crude fiber of 0.53%, crude protein of 8.28%, crude fat of 36.33%, and carbohydrates of 39.63%. Mineral analysis indicated notable concentrations of potassium at 1.1638 mg/L and calcium at 0.2046 mg/L, with sodium, manganese, zinc, iron, and copper detected in trace amounts. The study concludes that T. catappa seed nuts possess considerable nutritional and medicinal value, supporting their traditional applications and indicating their potential industrial use in food, pharmaceutical, and personal care products. These findings contribute to phytochemical and nutritional research by providing empirical evidence on the bioactive and compositional properties of T. catappa seeds.